2014
DOI: 10.1155/2014/207489
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Oviposition Behavior of Field Collected Aedes Mosquitoes

Abstract: Wild femaleAedes aegyptiandAe.albopictuswere allowed to lay eggs in (i) ovitraps with different concentrations of NaCl, (ii) different coloured ovistrips, (iii) water from different sources, (iv) larva holding water, and different sized ovitraps for oviposition preference. Oviposition cycle was also studied in different photoperiod regimens. The number of eggs laid was observed to gradually decrease with increase in NaCl concentration in both the species. Experiments were conducted to determine egg laying pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
4
25
2
Order By: Relevance
“…In the present study, maximum number of egg rafts were found in the ovitrap contained water of paddy field followed by the water of pond, tap, drain and river but no egg rafts were laid in the well water which is in contrast to the findings of our previous report of Panigrahi et al, (2014) where maximum number of eggs were laid by female Aedes mosquitoes in distilled water.…”
Section: Influence Of Water Collected From Different Sources On Ovipocontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, maximum number of egg rafts were found in the ovitrap contained water of paddy field followed by the water of pond, tap, drain and river but no egg rafts were laid in the well water which is in contrast to the findings of our previous report of Panigrahi et al, (2014) where maximum number of eggs were laid by female Aedes mosquitoes in distilled water.…”
Section: Influence Of Water Collected From Different Sources On Ovipocontrasting
confidence: 99%
“…In the present experiment too, the gravid females of Cx. quinquefasciatus preferred larval holding water over distilled water for oviposition which is also similar to the findings of Panigrahi et al, (2014) on Ae. albopictus and Ae.…”
Section: Influence Of Larva Holding Water On Oviposition Behaviorsupporting
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, the oviposition substrate is the only component of the ovitrap that is renewed at each examination, and variation in its sizes may considerably influence data and costs of the monitoring. Several studies have been conducted to understand how to improve the efficacy of ovitraps, focusing on the colors of the vessel (Hoel et al 2009, 2011, Panigrahi et al 2014 or on the use of chemical attractants (Anderson et al 2014, Santana et al 2006, Wang et al 2006, Thavara et al 2004 Centre for Disease Prevention and Control 2012), but no studies have investigated which sizes of oviposition substrate were the best.…”
Section: Introductionmentioning
confidence: 99%